A novel gas-assisted microcellular injection molding method for preparing lightweight foams with superior surface appearance and enhanced mechanical performance. (5th August 2017) - Hou, Junji; Zhao, Guoqun; Wang, Guilong; Dong, Guiwei; Xu, Jiaju
Abstract: This paper proposed a novel gas-assisted microcellular injection molding (GAMIM) method by combining the gas-assisted injection molding (GAIM) with the microcellular injection molding (MIM). Firstly, under the assistance of the high-pressure gas from the GAIM, the amount of the polymer melt required for fully filling the mold cavity is reduced in the GAMIM compared with that in the MIM, thus leading to a high weight reduction of the foamed part. Secondly, the high-pressure assisted gas from the GAIM can dissolve all the cells generated in the melt filling stage back into the polymer melt, thus improving the molded part's surface appearance by eliminating the surface sliver marks. Thirdly, the secondary foaming process in a steady state triggered by releasing the high-pressure assisted gas makes the foamed part have a fine cellular structure and a compact solid skin layer, which can help to enhance the part's mechanical properties. In order to verify the effectiveness of the GAMIM, comparison experiments of the MIM and the GAMIM were conducted. The results demonstrate that the GAMIM can not only significantly increase the weight reduction, but also greatly improve the surface appearance and mechanical properties of the foamed part. Graphical abstract: Highlights: A gas-assisted microcellular injection molding method is proposed. The method can significantly reduce the weight of the foamed part. The foamed part's surface appearance and mechanical properties are greatly improved by using this method.